2017
DOI: 10.1371/journal.pone.0178927
|View full text |Cite
|
Sign up to set email alerts
|

Serum N-glycome characterization and anti-carbohydrate antibody profiling in oral squamous cell carcinoma patients

Abstract: Glycosylation is a protein post translational modification which plays important role in protein function, stabilization, trafficking, and turnover. Alteration of protein glycosylation is a common phenomenon during tumor progression, migration, invasion, angiogenesis, as well as metastasis. Hence, aberrant glycan structures and the induced corresponding anti-carbohydrate antibodies are potential biomarkers for cancer diagnosis. In this study, serum N-glycomes and anti-carbohydrate antibodies from normal popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…For example, no studies describing the specific glycopeptide profiles of head and neck cancers exist. Only one study with released serum N ‐glycans (as opposed to N ‐glycopeptides in our study) in OSCC has been published . This study had only three glycan compositions common with our study:…”
Section: Discussionmentioning
confidence: 97%
“…For example, no studies describing the specific glycopeptide profiles of head and neck cancers exist. Only one study with released serum N ‐glycans (as opposed to N ‐glycopeptides in our study) in OSCC has been published . This study had only three glycan compositions common with our study:…”
Section: Discussionmentioning
confidence: 97%
“…In our previous studies we found that fucosylation and especially core-fucosylation is enhanced in oral cancer cells relative to normal gingival keratinocytes [ 22 ]. We have also identified several serum N -glycans that can serve as valuable biomarkers for oral cancer diagnosis [ 23 ]. To further identify novel biomarkers for the early diagnosis of oral cancer, corefucosylated serum glycoproteins of normal volunteers and patients were purified by lectin chromatography, and the alteration of glycoproteins was analyzed by electrophoresis and mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the glycosylation patterns in oral cancer within diverse biological specimens including in cell lines ( 12, 20 ), tumour tissues ( 24 ), saliva ( 13, 21, 25 ), blood ( 13 ), plasma ( 26 ) and serum ( 27, 28 ) in attempts to uncover changes related to cell transformation ( 12 ) and with disease progression ( 13 ). Most of those studies evaluated the total levels of specific glycans or glycan features ( 13, 21, 24, 26 ) using relatively simple analytical techniques such as lectin-based strategies ( 24, 26, 27 ) and MALDI-MS profiling ( 12, 20, 27, 28 ) not able to survey the glycoproteome in an unbiased and quantitative manner with glycan fine structure and site-specific information ( 29 ). Our study is the first to use integrated glycomics and glycoproteomics to provide detailed insights into the heterogenous N -glycoproteome of OSCC tumour tissues obtained from a valuable cohort of patients with and without lymph node metastasis, a principal prognostic factor in OSCC ( 3, 30, 31 ).…”
Section: Discussionmentioning
confidence: 99%